Language games under Knightian uncertainty about types - Zhaojun Xing (Bielefeld University, Center for Mathematical Economics (IMW), 2021)
We concern a sender-receiver game of common interests having infinite types, e.g the set [0; 1]², but with finite signals. In our paper, we extend the game by introducing multiple priors over the type space and use incomplete preferences in Bewley's way. We characterize the equilibria under incomplete preferences by E-admissibility. Besides, it has the equivalence between the equilibria and Voronoi languages. Further, we demonstrates the existence of the indeterminacy of the game. At last, we present that vague words, e.g. cheap, big, red, etc., exist in the Knightian worlds but not in the Bayesian worlds, which means that vagueness comes from the way we view the world in Knightian method.
urn:nbn:de:0070-pub-29588491
Keywords: 519; Sprache; Spieltheorie; Philosophie; Theorie